Spline-based medial axis transform representation of binary images. (August 2021) - Wang, Jieying; Kosinka, Jiří; Telea, Alexandru
Highlights: We present a spline-based medial axis transform representation of binary images. Our method achieves very high compression ratios while keeping quality high. Our method has better performance than regular medial axis transform representation. We show how our method enables generating super-resolution images. We show how our method allows shape manipulation and captures multiscale skeletons. Graphical abstract: Abstract: Medial axes are well-known descriptors used for representing, manipulating, and compressing binary images. In this paper, we present a full pipeline for computing a stable and accurate piece-wise B-spline representation of Medial Axis Transforms (MATs) of binary images. A comprehensive evaluation on a benchmark shows that our method, called Spline-based Medial Axis Transform (SMAT), achieves very high compression ratios while keeping quality high. Compared with the regular MAT representation, the SMAT yields a much higher compression ratio at the cost of a slightly lower image quality. We illustrate our approach on a multi-scale SMAT representation, generating super-resolution images, and free-form binary image deformation.